Domestic River Water Use and Risk of Typhoid Fever: Results From a Case-control Study in Blantyre, Malawi. (30th May 2019) - Gauld, Jillian S; Olgemoeller, Franziska; Nkhata, Rose; Li, Chao; Chirambo, Angeziwa; Morse, Tracy; Gordon, Melita A; Read, Jonathan M; Heyderman, Robert S; Kennedy, Neil; Diggle, Peter J; Feasey, Nicholas A
Abstract: Background: Typhoid fever remains a major cause of morbidity and mortality in low- and middle-income settings. In the last 10 years, several reports have described the reemergence of typhoid fever in southern and eastern Africa, associated with multidrug-resistant H58 Salmonella Typhi. Here, we identify risk factors for pediatric typhoid fever in a large epidemic in Blantyre, Malawi. Methods: A case-control study was conducted between April 2015 and November 2016. Cases were recruited at a large teaching hospital, and controls were recruited from the community, matched by residential ward. Stepwise variable selection and likelihood ratio testing were used to select candidate risk factors for a final logistic regression model. Results: Use of river water for cooking and cleaning was highly associated with risk of typhoid fever (odds ratio [OR], 4.6 [95% confidence interval CI, 1.7–12.5]). Additional risk factors included protective effects of soap in the household (OR, 0.6 [95% CI, .4–.98]) and >1 water source used in the previous 3 weeks (OR, 3.2 [95% CI, 1.6–6.2]). Attendance at school or other daycare was also identified as a risk factor (OR, 2.7 [95% CI, 1.4–5.3]) and was associated with the highest attributable risk (51.3%). Conclusions: These results highlight diverse risk factors for typhoid fever in Malawi, with implications for control in addition to the provision of safe drinking water. There is an urgent need to improve our understanding of transmission pathways of typhoid fever, both to develop tools for detecting S . Typhi in the environment and to inform water, sanitation, and hygiene interventions. Abstract : This study identifies major water, hygiene, and social risk factors in Blantyre, Malawi, highlighting the importance of understanding our interactions with water sources beyond drinking water for better control of typhoid fever.